The Lost : The Black Room - Cross, Gillian (New York Oxford University Press, 2007)
At the end of The Dark Ground, Robert finally managed to escape from the tiny underground world in which he had found himself trapped. He needed Lorn's help to do it, and he had to leave her behind. Now, back in his own world and his own size again, he realises that Lorn will die if she has to spend the winter underground.